Advanced heterogeneous catalysts volume 1: applications at the nano-scale - Sudarsanam, Putla; Singh, Lakhveer (American Chemical Society, 2020)

Advanced heterogeneous catalysts volume 2: applications at the single-atom scale - Sudarsanam, Putla; Singh, Lakhveer (American Chemical Society, 2020)

Advances in single-atom catalysts for lignin conversion - Halilu, Ahmed; Umar, Ahmad Abulfathi; Balarabe, Yahaya Umar; Haniffa, Mhd. Abd. Cader Mhd.; Munawar, Khadija; Sunku, Kiran; Sudarsanam, Putla (Advanced Heterogeneous Catalysts Volume 2: Applications at the Single-Atom Scale, 2020)
Single-atom catalysts (SACs) have drawn significant attention as promising surfaces for promoting observable reaction processes. As a guideline, SACs should have the proper nanoscale dimensionality to influence their effective and efficient performance, especially during lignin conversion to platform chemicals and other useful products. The development of SACs for functional applications still has many difficulties, such as harnessing and improving low-coordinated metal atoms to have controlled and observable activities per metal atom. Consequently, the need arises to ensure a decrease in the size of the metal particles and their uniform dispersion or coordination on a suitable support material. This has been an industrial target for a long time in the field of catalysis. Supported metal-based catalysts are not dimensionally uniform, thereby reducing their metal-atom efficiency and frequently leading to undesired side reactions that are sometimes difficult to observe. This makes the identification of the active sites responsible for the reaction of interest very difficult or even impossible. To ameliorate this challenge, the ultimate small-size limit for a metal particle is the SAC, which contains isolated metal atoms singly dispersed on any suitable support materials. It is expected that SACs should maximize the metal-atom efficiency with respect to the application, which is particularly significant for supported metal catalysts. Moreover, through uniform single-atom dispersion, SACs offer a great opportunity for achieving high activity and tuning selectivity to the desired product. This chapter provides a comprehensive overview of recent advances in using SACs for the conversion of lignin or lignin model compounds. The different support materials used for SACs, such as zeolites, metal oxides, and carbonaceous and siliceous materials, are discussed. This contribution also covers the catalytic reactions of lignin with an emphasis on cleaving its specific linkages, along with a systematic evaluation of SACs used in the relevant processes. The chapter also addressed key parameters essential for tailoring the particle size and acid–base and redox properties of the SACs used in lignin conversion. Special attention is paid to understanding the role of synthesis conditions in tailoring the size of SACs. It is expected that this contribution will provide future directions for practical SAC development and implementation in lignin conversion.

Bifunctional rice husk-derived SiO2-Cu-Al-Mg nanohybrid catalyst for one-pot conversion of biomass-derived furfural to furfuryl acetate - Hashim, Luqman H.; Halilu, Ahmed; Sudarsanam, Putla; Umar, Yahaya Balarabe; Bin Johan, Mohd Rafie; Bhargava, Suresh K. (Fuel, 2020)
Developing one-pot reaction methodologies, which typically require multifunctional catalyst systems, is crucial for sustainable production of bio-derived fuels and chemicals. This work reports one-pot hydrogenation-esterification of furfural to furfuryl acetate using a bifunctional metal-based nanohybrid catalyst, composed of rice husk (RH) derived SiO2, Cu, Al, and Mg species (RHSiO2-Cu-Al-Mg). For comparison, the catalytic efficiency of RHSiO2-Cu and RHSiO2-Cu-Al were tested under similar reaction conditions. Various analytical techniques were used to elucidate the physicochemical, textural, and acid-redox properties of the catalysts. It was found that the RHSiO2-Cu-Al-Mg catalyst contains an optimum amount of acid and redox sites, as illustrated by NH3-TPD and H-2-TPR studies, respectively. Especially, Mg addition played a vital role in tailoring acidity of the RHSiO2-Cu-Al catalyst to promote in-situ esterification of furfuryl alcohol with acetic acid to yield furfuryl acetate. As a result, the RHSiO2-Cu-Al-Mg catalyst exhibited the best performance in one-pot conversion of furfural to furfuryl acetate, outperforming various noble metal/silica based catalysts. This study offers potential opportunities for the rational design of novel, bifunctional heterogeneous catalysts for efficient production of bio-derived fuels and value added chemicals.
Keywords: Acid-redox sites; Bifunctional catalyst; Bio-oil upgrading; One-pot furfural conversion; Rice husk silica

Bimetallic palladium nickel nanoparticles anchored on carbon as high-performance electrocatalysts for oxygen reduction and formic acid oxidation reactions - Goswami, Chiranjita; Saikia, Himadri; Tada, Kohei; Tanaka, Shingo; Sudarsanam, Putla; Bhargava, Suresh K.; Bharali, Pankaj (ACS Applied Energy Materials, 2020)
{Herein, we report the synthesis of carbon-supported palladium-nickel electrocatalysts (ECs) (Pd4-xNix/C ECs
Keywords: electrocatalysts; Formic Acid Oxidation; fuel cells; oxygen reduction reaction; palladium-nickel alloy

Catalytic biomass valorization - status and perspectives - Sudarsanam, Putla (Biomass Conversion and Biorefinery, 2020)

Functionalized magnetic nanosized materials for efficient biodiesel synthesis via acid-base/enzyme catalysis - Wang, Anping; Sudarsanam, Putla; Xu, Yufei; Zhang, Heng; Li, Hu; Yang, Song (Green Chemistry, 2020)
According to the principles of green chemistry, the rapid recovery and reuse of catalysts after a catalytic reaction are important factors to realize the sustainable management of chemical production processes. The functionalization of magnetic nanoparticles is the basis for the efficient separation of heterogeneous catalysts from the reaction system by using the magnetic separation technology as well as for effectively bridging heterogeneous and homogeneous catalytic processes. This can considerably improve the production efficiency and reduce energy consumption as well. Owing to important applications as a potential biofuel or fuel additive, the synthesis of biodiesel mainly from low-cost biomass feedstocks has received considerable attention in the current biorefinery research. A simple synthesis process coupled with the application of functionalized magnetic catalysts can remarkably reduce the production cost and minimize waste generation, thereby promoting the potential development of green catalytic processes for the large-scale synthesis of biodiesel. In this review, the preparation methods, structural and performance control, and protection and functionalization of magnetic nanoparticles as well as the consequent catalytic effects in the synthesis of biodiesel (mainly long-chain fatty acid methyl esters) have been reported. In addition, various representative reaction mechanisms are discussed, emphasizing the existing challenges and prospects of industrialization.

Highly dispersed MnOx nanoparticles on shape-controlled SiO2 spheres for ecofriendly selective allylic oxidation of cyclohexene - Rao, Bolla Govinda; Sudarsanam, Putla; Rao, Tumula Venkateshwar; Amin, Mohamad Hassan; Bhargava, Suresh K.; Reddy, Benjaram M. (Catalysis Letters, 2020)
Shape-controlled metal nanomaterials are considered as a unique class of catalysts because of their synergistic size- and shape-dependent catalytic properties. This work reports the synthesis of a novel size- and shape-controlled catalyst, consisting of highly dispersed MnOx nanoparticles (average particle size of 4.5 nm) on shape-controlled SiO2 nanospheres (250-300 nm) for selective cyclohexene oxidation using air as the oxidant under solvent- and base-free conditions. The MnOx/SiO2 catalyst exhibited an excellent cyclohexene conversion (92%) with a high selectivity (96%) to the allylic products (2-cyclohexene-ol and 2-cyclohexene-one) under mild conditions, outperforming various SiO2 supported CoOx, FeOx, and CuOx catalysts. The better performance of shape-controlled MnOx/SiO2 nanocatalyst is due to high redox nature of Mn, uniform dispersion of smaller sized MnOx nanoparticles, and synergetic interaction between MnOx and SiO2 spheres, as evidenced by XPS and TEM studies. Further, the MnOx/SiO2 catalyst could be reused at least 5 times for selective cyclohexene oxidation with a negligible loss in its catalytic performance, indicating the excellent stability of shape-controlled metal nanocatalysts in organic synthesis under economically viable and mild conditions.
Keywords: Cyclohexene oxidation; MnOx nanoparticles; Shape-controlled catalyst; SiO2 nanospheres; Structure-performance relationship; Synergetic interaction

TiO2-based water-tolerant acid catalysis for biomass-based fuels and chemicals - Sudarsanam, Putla; Li, Hu; Sagar, Tatiparthi Vikram (ACS Catalysis, 2020)
Solid acid catalysts alone or in combination with redox metals play a pivotal role in biomass valorization to obtain alternative fuels and chemicals. In acid-catalyzed biomass conversions, water is a key reagent/byproduct that can induce leaching/poisoning of catalyst's acid species, a major problem toward catalyst recyclability and product purification. Thus, developing efficient water-tolerant solid acid catalysts is vital for viable biomass valorization. TiO2 is considered to be a promising water-tolerant solid acid catalyst for biomass conversions because of the presence of coordinatively unsaturated Ti4+ sites, which are robust and less prone to leaching in the aqueous medium. Besides, the synergistic combination of TiO2 with redox metals (Ru, Pd, Ni, Cu, etc.) provides abundant bifunctional acid-redox sites, which exhibit a favorable catalytic role in the deoxygenation of biomass molecules to practically useful hydrocarbons. Therefore, this review provides an overview of recent progress toward TiO2-based water-tolerant acid catalysis for biomass conversion, with a focus on hydrothermal stability of TiO2, its acidity, and catalysts' synthesis methods. Various biomass conversions over TiO2-based catalysts, where water-tolerant acid sites or acid-redox dual sites show a significant catalytic effect, were discussed. Structure-activity relationships based on water-tolerant Lewis acidity of TiO2 were emphasized. We believe that this review will provide valuable information for developing efficient water-tolerant solid acid catalysts not only for biomass valorization but also for other challenging reactions in the aqueous medium.
Keywords: Acid catalysis; acid-redox catalysis; Biomass conversion; renewable fuels and chemicals; TiO2-based catalysts; water-tolerant Lewis acidity

Towards lignin-derived chemicals using atom-efficient catalytic routes - Sudarsanam, Putla; Ruijten, Dieter; Liao, Yuhe; Renders, Tom; Koelewijn, Steven-Friso; Sels, Bert F. (Trends in Chemistry, 2020)
Lignin is a potential non-fossil resource of diverse functionalized phenolic units. The most important lignin- derived monomers are 4-alkylphenols, 4- hydroxybenzaldehydes, 4-hydroxybenzoic acids, and 4-hydroxycinnamic acids/esters. Efficient transformation of lignin and/or its monomers into valuable aromatics and their derivatives is crucial, not only for a sustainable lignocellulose biorefinery, but also to reduce our dependence on fossil feedstocks. This review provides a concise account of the recent advances in lignocellulose fractionation/lignin depolymerization processes towards lignin-derived monomers. Subsequently, numerous potential atom-efficient catalytic routes for upgrading lignin monomers into drop-in chemicals and new polymer building blocks are discussed.

Reusable magnetic nanocatalyst for bio-fuel additives: the ultrasound-assisted synthesis of solketal dagger - Rajkumari, Kalyani; Changmai, Bishwajit; Meher, Ananta Kumar; Vanlalveni, Chhangte; Sudarsanam, Putla; Wheatley, Andrew E. H.; Rokhum, Samuel Lalthazuala (Sustainable Energy & Fuels, 2021)
Acetalization of glycerol into solketal, a potential fuel additive, is a promising approach to utilizing the large waste-stream of glycerol from the biodiesel industry. Herein, we report an efficient ultrasound-assisted room temperature synthesis of solketal by acetalization of glycerol with acetone using an easily recoverable sulfonic acid-functionalized, silica-coated Fe3O4 magnetic nanoparticle (Fe3O4@SiO2@SO3H MNP, FSS MNP) catalyst. The morphology, chemical composition and magnetic properties of the catalyst were elucidated. The acetalization of glycerol was carried out under ultrasonication at room temperature, resulting in 97% glycerol conversion after 15 minutes and 95% isolated yield of solketal with 100% selectivity for this acetal. The facile magnetic retrievability of the catalyst imparted operational simplicity to the solketal synthetic protocol, avoiding complicated catalyst separation and product purification processes. The FSS catalyst was magnetically recycled for up to five catalytic experiments, maintaining a glycerol conversion of 95% and without deterioration in its selectivity, composition, morphology or magnetic properties, thereby ameliorating the green aspects of the protocol.

Room-temperature quasi-catalytic hydrogen generation from waste and water - Wu, Hongguo; Zhang, Li-Long; Wang, Junqi; Jiang, Yiyuan; Li, Hu; Sudarsanam, Putla; Yang, Song (Green Chemistry, 2021)
A solvation-driven catalyst-free H-2 generation system from water and various waste hydrosilanes at room temperature was developed, with good to quantitative H-2 yields in minutes. Using a green solvent is found to promote the strong coordination of proton carriers with hydrosilane to liberate H-2 based on molecular dynamics simulations. Theoretical calculations clarify that OH(-)in situ generated from H2O enabled by solvation is favorable for activating the Si-H species of hydrosilane, and the in situ formed Si-OH interacts more effectively with the adjacent remaining Si-H, both contributing to the overall enhanced H-2 generation. Moreover, the overall life-cycle impacts of the developed system are less than those of industrial H-2 production processes, especially in ozone layer depletion and abiotic depletion resources - fossil fuels. This protocol realizes the potential of efficiently producing H-2 from waste and water, and opens a new avenue to alleviate petroleum consumption.

Sulfonic acid-functionalized heterogeneous catalytic materials for efficient biodiesel production: a review - Tan, Xiang; Sudarsanam, Putla; Tan, Jinyu; Wang, Anping; Zhang, Heng; Li, Hu; Yang, Song (Journal of Environmental Chemical Engineering, 2021)
The development of social productive forces leads to the increasing consumption of fossil fuels. However, the burning of traditional fossil fuels releases huge amounts of carbon emissions into the atmosphere, resulting in drastically increased global surface temperatures, and hence, global warming and abnormal climate change. Biodiesel, which can be produced by (trans)esterification of bio-oils using solid acid catalysts, is recognized as renewable and clean energy, alternative to fossil-derived diesel, and it can meet society's requirements. This review describes the catalytic conversion of bio-derived oils into biodiesel using various sulfonic acid-functionalized heterogeneous catalytic materials that show higher catalytic efficiency and superior recyclability. Besides, various methods of biodiesel preparation and the appropriate design and preparation of robust and efficient catalytic materials for biodiesel production were provided. Finally, the mechanisms of different catalytic esterification and transesterification reactions for biodiesel synthesis, the relevant reaction kinetic models, and techno-economic analysis of biodiesel production were critically discussed in this review.
Keywords: (Trans)esterification; Biodiesel; heterogeneous catalysis; kinetic study; solid acid

Supported MoOx and WOx solid acids for biomass valorization: interplay of coordination chemistry, acidity, and catalysis - Sudarsanam, Putla; Gupta, Navneet Kumar; Mallesham, Baithy; Singh, Nittan; Kalbande, Pavan Narayan; Reddy, Benjaram M.; Sels, Bert F. (ACS Catalysis, 2021)
Supported molybdenum oxide (MoOx) and tungsten oxide (WOx) materials are a vital class of solid acid catalysts for the chemical industry because of their nontoxic nature, strong acidity, remarkable stability in water, hydrogen, and oxygen atmospheres, and excellent reusability performance. These fascinating solid acids play a pivotal role in developing sustainable catalytic routes for renewable biomass processing to produce value-added fuels, chemicals, and platform molecules. The coordination chemistry of MoOx and WOx on the support materials (oxides, carbons, or zeolites) controls their acidic strength, active site accessibility, and catalytic activity. Hence, significant efforts have been made toward optimizing the conditions used for catalyst synthesis and biomass processing to tune the coordination chemistry of MoOx and WOx with the substrate molecules and, thus, their acid-activity/selectivity performance. This Review provides a comprehensive overview of supported MoOx and WOx solid acids for biomass valorization. The importance of the biomass and the role of solid acids for biomass valorization were emphasized, followed by a brief discussion of supported MoOx and WO(x )solid acids. Afterward, the interplay of coordination chemistry, acidic strength, and catalytic activity of supported MoOx and WOx solid acids was discussed. Finally, their catalytic applications for the valorization of several biomass substrates and their derivatives were summarized. This Review will provide valuable insights for developing advanced supported WOx and MoOx solid acids for catalytic biomass valorization and other challenging acid-catalyzed processes.
Keywords: Acidity; biomass valorization; catalysis; Coordination chemistry; molybdenum oxide; tungsten oxide

Synergistic nanostructured MnOx/TiO2 catalyst for highly selective synthesis of aromatic imines - Sudarsanam, Putla; Kockritz, Angela; Atia, Hanan; Amin, Mohamad Hassan; Bruckner, Angelika (ChemCatChem, 2021)
This work reports the development of a synergistic nanostructured MnOx/TiO2 catalyst, with highly dispersed MnOx nanoparticles (4.5 +/- 1 nm) on shape-controlled TiO2 nanotubes (8-11 nm width and 120-280 nm length), for selective synthesis of valuable aromatic imines at industrially important conditions. Pristine TiO2 nanotubes exhibited 97 % imine selectivity at a 38.3 % benzylamine conversion, whereas very low imine selectivity was obtained over commercial TiO2 materials, indicating the catalytic significance of shape-controlled TiO2 nanotubes. The MnOx nanoparticle/TiO2 nanotube (10 wt% Mn) catalyst calcined at 400 degrees C showed the best activity with 95.6 % benzylamine conversion and 99.9 % imine selectivity. This catalyst exhibited good recyclability for four times and is effective for converting numerous benzylamines into higher yields of imines. The high catalytic performance of MnOx/TiO2 nanotubes was attributed to higher number of redox sites (Mn3+), high dispersion of Mn species, and shape-controlled structure of TiO2, indicating that this catalyst could be a promising candidate for selective oxidation reactions.
Keywords: Acid-redox properties; aerobic oxidation; Nanostructured catalyst; Selective catalysis; Synergistic metal-oxide interaction

Efficient cascade C-N coupling reactions catalyzed by a recyclable MoOx/ Nb2O5 nanomaterial for valuable N-heterocycles synthesis - Singh, Nittan; Kalbande, Pavan Narayan; Umbarkar, Shubhangi; Sudarsanam, Putla (Molecular Catalysis, 2022)
The efficient cascade synthesis of pharmaceutically valuable N-heterocycles at solvent-free conditions was achieved using a robust, recyclable MoOx/Nb2O5 nanocatalyst. The results of catalyst screening revealed that the MoOx/Nb2O5 nanorods, calcined at 500 degrees C (MoNb5), exhibit excellent catalytic activity in the oxidative coupling of benzylamine with 96.5% conversion and >99.6% selectivity to the desirable imine product. The uniform dispersion of Mo-oxide nanoparticles (average particle size: 5.2 +/- 0.5 nm) on shape-controlled Nb2O5 nanorods (width: 5.3 +/- 0.5 nm and length: 23-38 nm) in MoNb5 catalyst led to improved structural and acid properties, beneficial for the cascade C-N bond construction. The shape-controlled MoNb5 catalyst showed versatile activity in various cascade C-N coupling reactions to obtain 2-phenylbenzimidazole, 2-phenyl-quinaxoline, and 2-phenyl-2,3-dihydroquinazolin-4(1H)-one with good to excellent yields at solvent-free con-ditions. The optimum ratio of Lewis/Bronsted acid sites, the unique structure of Nb2O5 nanorods, and the strong MoO3-Nb2O5 interaction are the key reasons for the higher activity of MoNb5 catalyst. The efficient reusability of MoNb5 catalyst, its remarkable activity in diverse N-heterocycles synthesis, and efficient gram-scale synthesis emphasize its practical application for the cascade C-N coupling reactions under benign conditions.
Keywords: Acid sites optimization; Cascade C-N bond formation; Diverse nitrogenous chemicals; Heterogeneous nanosized catalyst; MoO3-Nb2O5 interaction; Nb2O5 nanorods

Efficient synthesis of 5-(hydroxymethyl)furfural esters from polymeric carbohydrates using 5-(chloromethyl)furfural as a reactive intermediate - Bhat, Navya Subray; Hegde, Shobhita L.; Dutta, Saikat; Sudarsanam, Putla (ACS Sustainable Chemistry & Engineering, 2022)
This work reports an efficient, gram-scale synthesis of 5-(hydroxymethyl)furfural (HMF) esters using biomass-derived 5-(chloromethyl)furfural (CMF) as a reactive intermediate. The HMF-esters have potential applications as chemicalintermediates, fuel additives, and bioactive compounds. Initially, CMF was prepared in good yields directly from polymericcarbohydrates (starch, inulin, and cellulose) and cellulosic materials (cotton andfilter paper) using a biphasic batch reaction system,consisting of aqueous hydrochloric acid and 1,2-dichloroethane. The use of ZnCl2as an additive allowed the reaction to proceedunder milder conditions while significantly improving the isolated yield of CMF. The effects of reaction temperature, reaction time,extracting solvent, and ZnCl2loading on CMF yield were investigated. Microcrystalline cellulose was converted into CMF with a72% isolated yield under optimized reaction conditions (80 degrees C, 2 h). After that, CMF was transformed into various novel esters ofHMF in excellent isolated yields (>85%) by reacting with a slight excess amount of the triethylammonium salt of various alkyl/arylcarboxylic acids under solvent-free conditions
Keywords: catalysis; cellulose; furanics; HMF-esters; renewable synthesis

Protophilic solvent-impelled quasi-catalytic CO2 valorization to formic acid and N-formamides - Wu, Hongguo; Li, Hu; Zhao, Wenfeng; Sudarsanam, Putla; Yang, Song (Fuel, 2022)
As a low-price and luxuriant C1 sustainable resource, CO2 has the privilege of synthesizing hydrogen carriers and valuable chemicals. However, expensive metallic and organic catalysts are often indispensable for going on wheels of the relevant reaction processes. In this work, a protophilic solvent-impelled quasi-catalytic system was developed for efficient synthesis of formic acid and various N-formamides with high yields of 76-94% via reductive CO2 functionalization under mild reaction conditions (50 ?). Direct activation of the liquid hydrosilane toward the reduction of CO2 enabled by DMSO with optimum basicity/protophilicity is the predominant reaction route among the examined interaction models, while carbonic acid potentially derived from excessive CO2 and residual water inhibits the reaction, as explicitly disclosed by theoretical calculations and isotope labeling experiments. In addition, the in situ formed O-formyl species is conductive to the cascade CO2 reduction steps, which remarkably facilitated the overall quasi-catalytic upgrading process.
Keywords: CO2 utilization; Formic acid; Green energy; Nitrogenous chemicals; Quasi-catalysis

Shape-controlled nanostructured MoO3/CeO2 catalysts for selective cyclohexene epoxidation - Sudarsanam, Putla; Singh, Nittan; Kalbande, Pavan Narayan (Catalysis Communications, 2022)
This study reported a vital role of CeO2 shape on the structure-activity properties of MoOx/CeO2 catalysts for cyclohexene epoxidation. Uniform dispersion of MoOx on the surface of shape-controlled CeO2 nanocubes (average particle size: 23.5 nm) and nanorods (average width: 6.3 nm and length: 15-95 nm) was found in MoOx/CeO2 nanomaterials. The MoOx/CeO2 nanocubes showed higher epoxide selectivity (97.3%) with 98.9% cyclohexene conversion, although it has lower BET surface area (30.2 m(2)/g) compared with MoOx/CeO2 nanorods (72.8 m(2)/g). The presence of more electropositive Mo6+ species and the strong Mo-Ce interaction led to improved catalytic efficacy of MoOx/CeO2 nanocubes in cyclohexene epoxidation.
Keywords: CeO2 nanocubes; CeO2 shapes; Nanosized MoOx/CeO2 catalyst; Selective epoxidation; Structure-activity properties

One-pot synthesized efficient molybdenum-niobium-oxide nanocatalyst for selective C-O and C-N coupling reactions at mild conditions - Kalbande, Pavan Narayan; Singh, Nittan; Swapna, Bhattu; Umbarkar, Shubhangi; Sudarsanam, Putla (Catalysis Communications, 2023)
An efficient molybdenum-niobium-oxide nanomaterial was synthesized by a one-pot hydrothermal method for selective C-O (glycerol ketalization) and C-N coupling (benzylamine oxidation) reactions. The catalytically favourable properties, such as defective metal sites, truncated surfaces, and uniform metal dispersion in the MoO3-Nb2O5 nanorods, calcined at 500 degrees C (MoNb OPS-5), were confirmed by Raman, HR-TEM, and STEM-EDX, respectively. Because of improved Lewis/Bronsted acidic strength, the MoNb OPS-5 catalyst showed higher activity in glycerol ketalization and benzylamine oxidation at mild conditions, giving superior selectivity to solketal (97%) and dibenzylimine (99%), respectively. The MoNb OPS-5 catalyst showed high structural stability and considerable good reusability efficacy.
Keywords: C-O and C-N coupling; Glycerol and benzylamine; Mo-Nb-O nanocatalyst; nanocatalysts; One-pot hydrothermal synthesis

Photocatalytic C-N bond construction toward high-value nitrogenous chemicals - Li, Jie; Liu, Tengyu; Singh, Nittan; Huang, Zhuochun; Ding, Yan; Huang, Jinshu; Sudarsanam, Putla; Li, Hu (Chemical Communications, 2023)
The construction of carbon-nitrogen bonds is vital for producing versatile nitrogenous compounds for the chemical and pharmaceutical industries. Among developed synthetic approaches to nitrogenous chemicals, photocatalysis is particularly prominent and has become one of the emerging fields due to its unique advantages of eco-sustainable characteristics, efficient process integration, no need for high-pressure H2, and tunable synthesis methods for developing advanced photocatalytic materials. Here, the review focuses on potential photocatalytic protocols developed for the construction of robust carbon-nitrogen bonds in discrepant activation environments to produce high-value nitrogenous chemicals. The photocatalytic C-N bond construction strategies and involved reaction mechanisms are elucidated. This review focuses on potential photocatalytic protocols developed for the construction of robust carbon-nitrogen bonds in discrepant activation environments to produce high-value nitrogenous chemicals.

Progressions in cathodic catalysts for oxygen reduction and hydrogen evolution in bioelectrochemical systems: Molybdenum as the next-generation catalyst - Mishra, Puranjan; Sudarsanam, Putla; Mahapatra, Durga Madhab; Elmekawy, Ahamad; Pant, Deepak; Singh, Lakhveer (Catalysis Reviews- Science and Engineering, 2023)
Oxygen reduction reactions (ORRs) are unanimously a key factor of system performances in bioelectrochemical systems (BESs), low-temperature fuel cells, and generally in several electrochemical platforms. Platinum (Pt)-based catalyst is the finest electrocatalyst for ORR in BESs; however, it is constrained by its low abundance, high price, and poor catalytic durability in an electrochemical setup for cathodic reaction kinetics. In recent years, significant efforts in trimming the metal-based catalyst up to nanoscale to cater high performance of ORR have been explored. Still, there are many opportunities to improve catalyst performance at cathode through proper selection of an efficient low-cost metal-based ORR catalyst. Molybdenum (Mo) with its multi-dimensional form as 2D and 3D layers and synergistic combination with other non-metals offers prospects of extraordinary performance as low-cost metal-based ORR catalyst over the Pt in delivering enhanced ORR potential. The present review throws light on current requirements of a sturdier catalyst material and thus provides a comprehensive review on the continuing efforts in exploring the possibility of Mo as a low-cost metal-based ORR catalyst. This literature analysis would enlighten the significance of ORR in BESs, followed by the electrochemistry of Mo-based cathodic catalyst, its underlying mechanism and performance limiting factors in the operation of ORR. Moreover, the extensive and systematic acumen in the context of Mo-based catalytic formulations for increased ORR potentials including nano-composite Mo-cathode catalyst; development of Mo-catalyst with varied configurations; carbon-supported Mo-catalyst; morphological changes; surface area modifications; and Mo-coupling with other transition metal and its derivatives were discussed in great detail to provide prospective application of Mo-based catalyst. Lastly, numerous opportunities and projections for future research in fabrication, juxtaposition, and implementation of Mo-based cathodic catalysts and consequent recommendations were discussed as conclusive remarks for bringing out the state-of-the-art review on this subject.
Keywords: Bioelectrochemical system; catalytic formulations; H-2-evolution reaction; Mo-based cathodic catalyst; multifunctional catalysts; oxygen reduction reaction

Shape-controlled MoO3/MnO x nanocatalyst for the selective synthesis of 2-phenylquinoxaline drug motifs - Singh, Nittan; Putla, Suresh Babu; Pratap Singh, Chandrodai; Kalbande, Pavan Narayan; Choudhary, Priyanka; Krishnamurty, Sailaja; Krishnan, Venkata; Bhatte, Kushal; Sudarsanam, Putla (ACS Applied Nano Materials, 2023)
We have developed a highly effective shape-controlled MoO3/MnOx nanocatalyst for the selective synthesis of 2-phenylquinoxaline drug motifs at room temperature without any external oxidant. Electron microscopy images reveal that the MnOx material contains rod-shaped particles (length: 500-1000 nm and width: 150-200 nm) and the MoO3 species are uniformly dispersed in the MoO3/MnOx material. The MoO3/MnOx nanocatalyst calcined at 500 degrees C (MoO3/MnOx-5) contains abundant strong acid sites and an optimum ratio of Mn4+/Mn3+, which are responsible for the C-N cross-coupling reaction between 2-phenylethylamine and o-phenylenediamine, giving higher yields (>96%) of 2-phenylquinoxaline at mild conditions. The broad scope of this catalytic strategy at room temperature and without an external oxidant was confirmed by achieving >90% yields of functional 2-phenylquinoxalines from C-N cross-coupling of various o-phenylenediamines and 2-phenylethylamines. The outstanding reusability efficiency of the MoO3/MnOx-5 nanocatalyst up to five cycles without the need for a regeneration step as well as the effective scalability highlighted the practicability of the MoO3/MnOx-based catalytic protocol for carbon-heteroatom coupling reactions at room temperature and without an external oxidant. Using computational studies, the possible reasons for the selective synthesis of 2-phenylquinoxaline over the MoO3/MnOx-5 nanocatalyst were elucidated.
Keywords: cascade C-N cross-coupling; DFT studies; room temperature andopen air; shape-controlled MoO3/MnOx nanocatalyst; structure-activity correlation

Durable and stable bifunctional Co3O4-based nanocatalyst for oxygen reduction/evolution reactions - Chutia, Bhugendra; Chetry, Rashmi; Rao, Komateedi N.; Singh, Nittan; Sudarsanam, Putla; Bharali, Pankaj (ACS Applied Nano Materials, 2024)
The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are recognized as the core reaction processes in regenerative energy storage and conversion systems. The design of cost-effective and high-performance bifunctional ORR/OER electrocatalysts (ECs) is very important for their substantial commercialization. Herein, sponge-like Co3O4 nanoparticles anchored on carbon (Sp-Co3O4/C) are successfully fabricated by a facile two-step solvothermal strategy for ORR/OER in an alkaline electrolyte. The Sp-Co3O4/C EC exhibits promising bifunctional ORR/OER activity with ORR onset potential (E onset = 0.88 V vs RHE), half-wave potential (E (1/2) = 0.75 V), limiting current density (j = -6.60 mA cm(-2)), OER onset potential (E-onset = 1.26 V), and OER overpotential for 10% energy conversion (eta(10) = 0.38 V) in 0.1 M KOH. It demonstrates a significantly lower reversibility index (Delta E = E- j10 - E 1/2 = 0.86 V), comparable to standard Pt/C and RuO2 ECs. The superior ORR/OER performances of Sp-Co3O4/C EC can be ascribed to the synergistic contribution of a high electrochemically active surface area (48.33 m(2) g(-1)), BET surface area (131 m(2) g(-1)), the rich interfacial structure of the crystal facets (111), (220), and (311), and the abundant oxygen vacancies in the sponge-like morphology. Besides the methanol tolerance, accelerated durability and chronoamperometric test established excellent durability and stability in the electrocatalytic operation. This work offers insight into the development of high-performance ORR/OER ECs. [GRAPHICS]
Keywords: bifunctional; fuel cell; interface; oxygen evolution; oxygen reduction; Oxygen vacancy; Sp-Co3O4/C; sponge-like morphology

Efficient glycolysis of used PET bottles into a high-quality valuable monomer using a shape-engineered MnO nanocatalyst - Swapna, Bhattu; Singh, Nittan; Patowary, Suranjana; Bharali, Pankaj; Madras, Giridhar; Sudarsanam, Putla (CATALYSIS SCIENCE & TECHNOLOGY, 2024)
Keywords: Catalyst; kinetics; Nanorods; Oxidation; Oxides; POLY(ETHYLENE-TEREPHTHALATE); WASTE

Selective synthesis of renewable diesel fuel precursors via C-C condensation of biomass-derived furans using a niobium oxide nanocatalyst - Kumar, Mudavath Arun; Swapna, Bhattu; Kalbande, Pavan Narayan; Yalagandula, Lavanya; Singh, Satyapaul A.; Sudarsanam, Putla (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2024)
Keywords: 2-Methylfuran; Catalysts; dehydration; NB2O5; RANGE ALKANES; solid acid; Valorization

Valorizing biomass waste glycerol to fuel additive at room temperature using a nanostructured WO3/Nb2O5 catalyst - Putla, Suresh Babu; Subha, P.; Swapna, Bhattu; Singh, Nittan; Sudarsanam, Putla (Catalysis Communications, 2024)
We developed a nanostructured catalyst consisting of WO3 nanoparticles and Nb2O5 nanorods for efficient glycerol acetalization to produce a fuel additive (solketal) at room temperature. Particularly, the WO3/Nb2O5 nanocatalyst calcined at 400 degrees C (WO3/Nb2O5-4) contains W5+ species and optimum acid sites, which enhanced glycerol conversion (92.3%) with 95.6% of solketal selectivity at room temperature. The structure stability of the WO3/Nb2O5-4 catalyst during the reaction is showcased by hot-filtration study and XRD/XPS characterization. However, the inadequate regeneration of the Bronsted acid sites led to a gradual decrease in the recyclable activity of the WO3/Nb2O5-4 catalyst.
Keywords: Bronsted-Lewis acid sites; Fuel additive; Room-temperature glycerol acetalization; W5+species

Additive-free, selective synthesis of N-heteroaromatics using morphology-engineered hollow CeO2 nanocatalyst - Singh, Nittan; Swapna, Bhattu; Balu, Alina Mariana; Bhatte, Kushal; Sudarsanam, Putla (ACS Sustainable Chemistry & Engineering, 2025)
We developed a highly efficient, shape-controlled CeO2 nanocatalyst for synthesizing N-heteroaromatics via an aerobic dehydrogenation approach, operating at mild reaction conditions without needing toxic acid/base additives. Different morphologies of CeO2, namely, hollow nanospheres, nanorods, and irregularly shaped nanoparticles, were synthesized, as confirmed by electron microscopy analysis. The CeO2 hollow nanosphere catalyst (CeO2-HNS) exhibited unique features, such as abundant acid-base sites, larger-sized voids, and surface oxygen vacancies. These characteristics are found to be crucial for the additive-free oxidative dehydrogenation of saturated N-heterocycles over the CeO2-HNS catalyst, resulting in 98% conversion of 1,2,3,4-tetrahydroquinoline with 100% quinoline product selectivity. The versatility of this approach was further demonstrated by the successful aerobic dehydrogenation of a broad range of saturated N-heterocycles, affording N-heteroaromatics in good to excellent yields. Furthermore, the CeO2-HNS nanocatalyst showed exceptional reusability over six cycles without requiring a regeneration step, such as high-temperature calcination treatment. The structural and morphological stability of the CeO2-HNS catalyst, along with reaction scalability and favorable green chemistry metrics, emphasized the practical viability of the CeO2-HNS catalyst for industrial applications.
Keywords: acid-base and defect sites; additive-free aerobicdehydrogenation; CeO2 hollow nanosphere catalyst; N-heteroaromatics; reusability and scalability

Liquid phase nitration of benzene to nitrobenzene using a mesoporous MoO3/Nb2O5 nanocatalyst - Kalbande, Pavan Narayan; Swapna, Bhattu; Sudarsanam, Putla; Umbarkar, Shubhangi B. (Catalysis Letters, 2025)
This work reports the synthesis of a mesoporous MoO3/Nb2O5 catalyst by a facile co-precipitation method for the liquid phase nitration of benzene to nitrobenzene, which is a vital industrial reaction. Pristine Nb2O5 and MoO3/Nb2O5 nanocatalysts were characterized using various techniques, including powder XRD, N-2 adsorption-desorption, Raman, SEM/TEM, pyridine FT-IR, and XPS. The MoO3/Nb2O5 catalyst (10 wt% MoO3 with respect to Nb2O5) showed uniform dispersion of Mo and Nb species, higher amount of oxygen vacancies, and more Br & oslash;nsted acid sites, resulting in a 90% yield of nitrobenzene. In contrast, only 35 and 58% yields were obtained in the case of commercial Nb2O5 and nanosized Nb2O5, respectively. The liquid phase nitration of benzene was carried out using commercial 65% HNO3 as a nitrating agent without sulfuric acid. The mesoporous MoO3/Nb2O5 catalyst is structurally stable, as confirmed by the characterization of the spent catalyst. However, a gradual decrease in the yield of nitrobenzene was observed, which could be due to the leaching of MoO3 species from the catalyst surface.
Keywords: Benzene nitration; Bronsted acid sites; Mesoporous MoO3/Nb2O5 Catalyst; nitrobenzene; Uniform metal dispersion